PREVALENCE, TREND AND ASSOCIATED FACTORS OF PHYSICAL ACTIVITY AMONG PERSONS WITH SELECTED DISABILITIES IN AMAHRA REGIONAL STATE, 2018/2019, ETHIOPIA - Andragachew, Mr. Yohannes; Haile (Assis. professor) , Temesgen; Worku, Mr. Habtamu; Alemu, Ms. Hawa; Tilahun, Mr. Seyoum Tilahun3; Alemu, Mr. Yonas; Tsega, Mr. Belaynew; Demeke, Mr. Wobdil; Kassa, Mrs. Meseret (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2022)
Introduction: Physical inactivity is a global public health problem, and it has been linked to many of the most serious illnesses facing many nations. Despite lots of research that has been published in the field of exercise science over the past three decades, there remains a paucity of information on the prevalence, trend and determinant factors of regular physical activity in persons with disabilities. Objective: To assess the prevalence and trend of physical activity and its associated factors among selected disabilities in Amhara regional state,2018/2019, Ethiopia Methods: Community based quantitative cross-sectional study design was conducted in Amhara regional state Ethiopia from December 15 to January 14, 2019. The study was included total of 5,250 (94.4% from the sample) persons with selected disabilities from Amhara regional state. The study participants were selected by using multi-stage sampling technique. Data was collected using different standard structured questionnaire. Multivariate logistic regression analysis was done to identify factors associated with regular physical activity. Finally, results were then presented with appropriate tables and graphs as well as Adjusted odds ratio (AOR) and 95% confidence interval. Results: - The prevalence of adequate physical activity among persons with selected disabilities was 34.9% (95% confidence Interval 31.9, 37.9). Being deaf, acquired a disability, having high physical environment motivators, Motivation for physical activity, attitude, and Commitment to Physical Activity were found to be significantly associated with adequate physical activity. Conclusion: - The prevalence of adequate physical activity among persons with selected disabilities in the Amhara regional state was low. Physical activity was higher among those with the disability of deaf, acquired disability, having high physical environment motivators, high motivation for physical activity, attitude, and Commitment to Physical Activity.